Revision of the dinoflagellate species composition of the Black Sea - Krakhmalnyi, A.F.; Okolodkov, Y.B.; Bryantseva, Yu.V.; Sergeeva, A.V.; Velikova, V.N.; Derezyuk, N.V.; Terenko, G.V.; Kostenko, A.G.; Krakhmalnyi, M.A. (Альгология, 2018)
Data on the diversity of dinoflagellates of the Black Sea (BS) obtained from all BS countries (Russia, Georgia, Turkey, Bulgaria, Romania and Ukraine) from 1886 to 2018 are critically ummarized. The revised list of the BS Dinoflagellata includes 420 species (447 including infraspecific taxa) from 92 genera that belong to 47 families, 16 orders and 4 classes.